Chronic Myeloid Leukaemia in Advanced Phase: An Analytical Evaluation - Sehar Khaliq, Sehar Khaliq (Journal of Rawalpindi Medical College, 2019)
Objective: To evaluate the clinical and morphological features in advanced phase chronic myeloid leukaemia. Methods: This descriptive observational study was conducted at the Pathology Unit of Fauji Foundation Hospital, Rawalpindi from June 2012 till June 2016. Diagnosed patients of chronic myeloid leukaemia in accelerated and blast phase of the disease were included in the study. History was taken, physical examination, complete blood counts, peripheral blood film examination, and bone marrow biopsy was done. Results: Mean age in the advanced phase was 47 years. Female to male ratio was 5:1. 19 patients were in blast phase ; 14( 74%) in myeloid transformation, 4(21%) patients in lymphoblastic transformation and 1(05%) patient transformed into acute biphenotypic leukaemia showing both lymphoid and myeloid markers. Forty six patients were in accelerated phase. Conclusion: There is usually not a single criterion for transition into accelerated phase but certain variables coexist at the same time.